The Influence of Booklet “Happy Entrepreneurship” toward the Entrepreneurship Motivation - Marlynda Happy Nurmalita Sari; Bekti Putri Harwijayanti (Jurnal Bidan Cerdas, 2022)
Intoduction: Students need to be motivated from an early age about entrepreneurship to be better prepared to become graduates who will create employment opportunities. Purpose: to know the effect of the booklet "Happy Entrepreneur" on the entrepreneurial motivation of Campus IV Blora Poltekkes Ministry of Health Semarang. Methods: Quasi-Experiment with Pretest and Posttest Control Group approach. Each sample is 27 students. Wilcoxon test for pre and post test in each treatment group and control group. Mann Whitney test to see pre-post differences between groups. Multiple logistic regression to see the most dominant variable. Results: There is a difference in motivation pre and posttest only in the treatment group (p value 0.000). There were differences in motivation in the treatment and control groups only in the posttest (p value 0.034). The results of the partial test in the pretest group, the supporting variable (p value 0.000) had a significant effect on entrepreneurial motivation. In the posttest group, the variables of knowledge (p value 0.042), family support (p value 0.001), and father's work (p value 0.013) had a significant effect on entrepreneurial motivation. Conclusion: There is an effect of giving “Happy Entrepreneurship” booklet media on students' knowledge in providing entrepreneurial motivation.